2015
DOI: 10.1371/journal.pone.0121401
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs with Apoptosis Regulating Potential Are Differentially Expressed in Chronic Exercise-Induced Physiologically Hypertrophied Hearts

Abstract: Physiological cardiac hypertrophy is an adaptive mechanism, induced during chronic exercise. As it is reversible and not associated with cardiomyocyte death, it is considered as a natural tactic to prevent cardiac dysfunction and failure. Though, different studies revealed the importance of microRNAs (miRNAs) in pathological hypertrophy, their role during physiological hypertrophy is largely unexplored. Hence, this study is aimed at revealing the global expression profile of miRNAs during physiological cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 33 publications
1
37
2
1
Order By: Relevance
“…In contrast, exercise training decreased cardiac miRNA-124 expression associated with an increase in their target gene PI3K (p110-␣) involved in physiological hypertrophy. Recently, Ramasamy et al (80) also performed microarray miRNA in swimming training-induced cardiac hypertrophy, indicating that miRNA-30e, -133b, and -208 were significantly upregulated and miRNA-99b and -100 were significantly downregulated after real-time PCR confirmation in healthy rats. Target genes that regulate proliferation and cell death were showed, suggesting that PI3/Akt/mTOR, MAPK, and p53 signaling are involved in physiological cardiac growth.…”
Section: Mirnas Cardiac Hypertrophy and Exercise Trainingmentioning
confidence: 99%
“…In contrast, exercise training decreased cardiac miRNA-124 expression associated with an increase in their target gene PI3K (p110-␣) involved in physiological hypertrophy. Recently, Ramasamy et al (80) also performed microarray miRNA in swimming training-induced cardiac hypertrophy, indicating that miRNA-30e, -133b, and -208 were significantly upregulated and miRNA-99b and -100 were significantly downregulated after real-time PCR confirmation in healthy rats. Target genes that regulate proliferation and cell death were showed, suggesting that PI3/Akt/mTOR, MAPK, and p53 signaling are involved in physiological cardiac growth.…”
Section: Mirnas Cardiac Hypertrophy and Exercise Trainingmentioning
confidence: 99%
“…miR-1, miR-133, miR199a/b, miR-21, miR-23, miR-26, miR-29, miR-9, miR-98, and miR-499) have been shown to exert either a positive or negative influence on pathological cardiac hypertrophy (4 -6). Whereas several studies have recently profiled microRNA expression signatures in rat physiological hypertrophic hearts induced by swimming or treadmill training, it still remains unknown how dys-regulated miRNAs contribute to physiological hypertrophy (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Among these, 16 miRNAs, including miR-222, were independently validated as concordantly regulated in both models . In a recent study, Ramasamy et al (2015) sequenced RNA from the hearts of rats swum for 8 weeks and sedentary controls and found that .80% of the 201 detected miRNAs were differentially regulated. Among the 128 miRNAs with read counts of .1000, 95 miRNAs were altered .1.5-fold with an adjusted false discovery rate (FDR) ,0.1 (Ramasamy et al 2015).…”
Section: Micrornas In Cardiovascular Exercise Responsementioning
confidence: 99%
“…In a recent study, Ramasamy et al (2015) sequenced RNA from the hearts of rats swum for 8 weeks and sedentary controls and found that .80% of the 201 detected miRNAs were differentially regulated. Among the 128 miRNAs with read counts of .1000, 95 miRNAs were altered .1.5-fold with an adjusted false discovery rate (FDR) ,0.1 (Ramasamy et al 2015). miRNAs changed .2.5-fold were miR208a, -19b, -133b, and -30e, which were all upregulated, and miR-99b, -100, -191a, -22, and -181a, which were all down-regulated.…”
Section: Micrornas In Cardiovascular Exercise Responsementioning
confidence: 99%